Outcomes of Treating a late case of Herpes Zoster Ophthalmicus masquerading as Orbital Cellulitis: A Case Report: Poster Presentation - Case Report - Ophthalmologist - JOSIAH IRMA; Saraswati Anindita Rizki; Jennifer Angelina; Jovita; Jennifer Handiokho (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction : Herpes zoster ophthalmicus (HZO) refers to a reactivated varicella-zoster virus involving the V1 nerve division. Although rare, previous reports have mentioned HZO cases masquerading as orbital cellulitis (HZO-OC). This report depicts the use of acyclovir, corticosteroids and citicoline in our HZO-OC patient with treatment delay. Case Illustration : A healthy 66 year old man presented to our clinic 4 weeks after signs of orbital cellulitis followed by vesicular rash following the CN V(1) dermatome were felt which was untreated. The right palpebra was edematous and erythematous. Hazy cornea, mixed injection, grade IV reverse RAPD, diminished direct and consensual reflex and external ophthalmoplegia of the right eye were noted. The diagnosis of HZO-OC with multiple cranial neuropathies OD was established. Topical and symptomatic treatment were given resulting no improvement. Ptosis of the right palpebra became present. The patient was then given systemic acyclovir, methylprednisolone and citicoline. Ophthalmoplegia improved after 2 months and ptosis improved after 4 months. Discussion : The use of systemic acyclovir and corticosteroids in HZO-OC patients were given promptly in previous literature. Multiple cranial nerve in our patient was thought to occur due to treatment delay. As improvement was not noted after topical treatment, these systemic treatments along with citicoline were added. Citicoline was added due to its ability to promote neural regeneration. Conclusion : Systemic acyclovir, corticosteroids and citicoline may still be beneficial for HZO-OC patients with delayed treatment.